Individual Investors Perception Towards Diversified Portfolio (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the most important factors of an individual investors investment portfolio is the lack of diversification. A wide range of possible alternatives is available for an investor to invest in the financial market. All these investment avenues vary from each other and are not equally decisive. The pat- tern of investment differs from investor to investor based on the reason behind the investment, withdrawal time, and risk- bearing capacity. The design and execution of a portfolio risk management program need not wait for all the bits of the puzzle to fall into place. Centralization of the portfolio management function may not be considered an optimal solution. A successful implementation necessitates a careful, well-articulated strategy to evaluate and address the key issues across the entire spectrum of investment risk management. Data requirements, dictated by the analytical model selected, can be significant but establishing implementation priorities will avoid inertia on this front. The individual’s decision of investment is prejudiced by the kind of services rendered and the benefits offered in the financial market. Financial knowledge and experience have an impact on the financial investment decision-making process. Investment Portfolio Diversification refers to selecting diverse classes of assets with the objective of risk minimization and returns/profit maximization. 94% of investors are preferring investments in Shares and 88% investors are investing in Bonds. 96% investors are holding mutual funds in their current portfolio. From recorded data it can be observed that, nowadays investors are inclined towards diversified investment portfolio.